Belgian and European perspectives on creditor protection in closed companies / Diederik Bruloot (editor). - Bruloot, D. (Diederik) (Intersentia, 2019)
This volume contains the papers presented during a workshop at Ghent University's Financial Law Institute. The aim of the workshop was to confront the new Belgian framework on creditor protection in closed companies with foreign experiences and insights from recent legal and empirical research. The book deals with questions of creditor protection throughout the lifespan of companies: from the time of their formation, over the different kinds of distributions, to their winding-up. Some contributions focus on more topical issues of creditor protection like the subordination of shareholder loans or the foreclosure of security interests. The book contributes to the continuing debate on the optimal legal strategy regarding creditor protection. Furthermore, it provides valuable insights on the background and foundations of the remarkable approach towards creditor protection in closed companies in the new 2019 Belgian Companies Act.Contributions by Diederik Bruloot and Evariest Callens, Isabelle Corbisier, Hans De Wulf, Miguel Gimeno Ribes, Frederic Helsen, Simon Landuyt, Christoph Van der Elst and Jasper Van Eetvelde.